1992
DOI: 10.1111/j.1745-4603.1992.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain Hardening of Dough as a Requirement for Gas Retention

Abstract: Mechanisms that can be responsible for the ability of wheat flour doughs to retain gas are discussed. It is concluded that the relevant types of physical instabilities are Ostwald ripening (disproportionation) and coalescence of gas cells. The extent of Ostwald ripening is probably primarily controlled by surface rheological properties; it certainly affects crumb structure, but it cannot explain the differences in gas retention among doughs from various cereals or various wheat cultivars. It is argued that sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(141 citation statements)
references
References 10 publications
6
134
0
1
Order By: Relevance
“…Previous studies 40 , in which the effect of WEP was studied, showed that addition of free FA led to a loss of gluten yield in the control sample (without WEP addition), but resulted in a higher gluten yield in the presence with WEP. Does free FA also give a higher gluten yield in the presence of WUS?…”
Section: Effect Of Fa On Gluten Yieldmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies 40 , in which the effect of WEP was studied, showed that addition of free FA led to a loss of gluten yield in the control sample (without WEP addition), but resulted in a higher gluten yield in the presence with WEP. Does free FA also give a higher gluten yield in the presence of WUS?…”
Section: Effect Of Fa On Gluten Yieldmentioning
confidence: 99%
“…In flour and dough, glutenin polymeric proteins are extremely polydisperse 39 , varying both in composition and size as reflected by differences in extractability. Moonen et al found that the SDS insoluble gel protein fraction highly correlated with SDS sedimentation values and loaf volume 40 . This fraction was later named the Glutenin Macro Polymer (GMP) to reflect the importance of glutenins and the highly aggregated nature of this fraction 41 .…”
Section: Factors Affecting Glutenin Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have mainly focused on the role of gluten proteins in determining the gas holding ability of dough. 1,2 In this respect, the strain hardening properties of dough/gluten are considered relevant. 1,2 However, some studies indicated that the contribution of a liquid film surrounding the gas cells is also relevant.…”
Section: Introductionmentioning
confidence: 99%